2007
DOI: 10.1103/physrevb.75.115201
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic modeling of the(a+c)-mixed dislocation core in wurtzite GaN

Abstract: An atomistic simulation of the threading ͑a + c͒-mixed dislocation core in wurtzite GaN has been carried out. Starting from models generated in the framework of continuum elasticity theory, two core configurations are obtained independently by using an empirical potential and a tight-binding based ab initio method. The most energetically favorable core with a 5 / 7-atoms ring structure is fully coordinated without wrong bonds, whereas the other with a complex double 5 / 6-atoms ring structure contains two rows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
1
34
1
Order By: Relevance
“…Theoretical predictions were also made using a Metropolis Monte Carlo method, with the positions of Ga and In atoms swapped at random within a cylindrical region of 4.46 nm around a dislocation core, and with differences in energies between trial configurations calculated by geometry optimization using the LAMMPS molecular dynamics code (MD) [30] and StillingerWeber potentials for InN [20] and GaN [31] Carlo simulations were continued until the total potential energy of the cell converged, and from this equilibrium core configurations were extracted. Further details of this model are available in our previous work [33].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical predictions were also made using a Metropolis Monte Carlo method, with the positions of Ga and In atoms swapped at random within a cylindrical region of 4.46 nm around a dislocation core, and with differences in energies between trial configurations calculated by geometry optimization using the LAMMPS molecular dynamics code (MD) [30] and StillingerWeber potentials for InN [20] and GaN [31] Carlo simulations were continued until the total potential energy of the cell converged, and from this equilibrium core configurations were extracted. Further details of this model are available in our previous work [33].…”
Section: Methodsmentioning
confidence: 99%
“…GPA was performed on the boxed region in the STEM-HAADF image in Figure 5 Furthermore, the STEM-HAADF image of a TD in Sample C (which does not contain any In) also shows a higher contrast near the TD core (as seen in Figure 6 As the double 5/6-atom core [31] and the 7-and the 9-atom rings at both ends of a dissociated 7/4/8/4/9-atom core [34] have all been suggested to introduce deep states in the GaN band gap, the new core structures observed for (a+c)-type TDs in In x Ga 1-x N films are likely to introduce additional states in the In x Ga 1-x N band gap. Therefore, the electronic properties of dislocations in In x Ga 1-x N are likely to be different from those in GaN.…”
mentioning
confidence: 99%
“…Since it has been observed that the GaN surfaces do not exhibit Fermi-level pinning, they were postulated to lack mid-gap states [6,7]. However, first-principles calculations for numerous dislocations, including partial dislocations [8,9],threading edge [10,11], screw [12], and mixed [13,14] dislocations, have shown that these dislocations all have deep-level states. Hence, GaN may not be immune to nonradiative recombination of its free carriers at its dislocations.…”
mentioning
confidence: 99%
“…These potentials have previously been used with success to study dislocations in GaN 26,28,29 InN 30 and In x Ga 1-x N alloys 31 including quantum dot systems 32 35 . There are sometimes multiple atomic configurations possible at the core for each Burgers vector, and these are typically referred to by the number of atoms in the atomic rings that make up the core.…”
mentioning
confidence: 99%
“…In this work, the 5/7-atom ring atype core is favored since it is considered to be the most stable 9 , though other core types are considered, while the 5/7-atom ring (a+c)-type core is not studied since it has not been observed experimentally 16 and instead the 9/4/7-atom ring (a+c)-type core is favoured. Likewise, only the most stable c-type core 38 , and the double-5/6-atom ring a+c-type core 28 were studied.…”
mentioning
confidence: 99%